The effectiveness of AI-assisted instruction for primary school students with mathematics learning disabilities - Wang Fangping; Nuraeni Ratna sari; Bingli Wang (Psychology, Evaluation, and Technology in Educational Research, 2025)
Despite the increasing application of artificial intelligence technology in education, research on the effectiveness of AI-assisted instruction systems for primary school students with mathematics learning disabilities remains limited. This study investigated the effects of a customized AI-assisted instruction system on improving academic performance and learning motivation among primary school students with mathematics learning disabilities. Using a quasi-experimental design, 42 third-to-fifth grade students diagnosed with mathematics learning disabilities from three primary schools in Jiangsu Province participated in a 12-week intervention study. The experimental group (n=21) received AI-assisted instruction intervention, while the control group (n=21) received traditional remedial instruction. The study collected data using standardized mathematics tests, learning motivation scales, and classroom observation records. Results showed that students in the experimental group demonstrated significant improvements in both mathematics achievement (Cohen's d=0.89) and learning motivation (Cohen's d=0.76). This article discusses strategies for effectively implementing AI-assisted instruction systems in special education settings.